Building Consumer Satisfaction of Poci Tea through Price Compatibility, Feeling and a Brand That is Easy to Remember - Warosatul Ammbiya; Annisa Rifa Nadia; Tantya Shifa Ramadhani; Wachdijono Wachdijono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Competition in the beverage industry is getting tighter, especially in tea drinks. One of the popular teas often included in the ranks of the top brand index is poci tea. However, there is a decrease in the tea percentage, indicating a decline in consumer satisfaction. This research aims to assess the impact of price variables on consumer satisfaction, mediated by product and brand image intervening variables. The study was conducted in Cirebon in July and August 2024. The type of research is descriptive quantitative. Based on the loading factor figure considered representative at 0.6, the sample size was determined at 114 poci tea respondents taken by accidental sampling. Data analysis is conducted using SEM (Structural Equation Modeling). The findings indicate no direct impact from price (X) on consumer satisfaction(Y3). Price (X) has a significant effect on the product variable (Y1) with a probability of 0.023, product (Y1) has a significant impact on the brand image variable (Y2) with a probability of 0.012, brand image (Y2) has a significant effect on consumer satisfaction variable (Y3) with a probability of 0.044. Moreover, price indirectly affects consumer satisfaction through product and brand image variables with a probability of 0.047.